Biological characteristics of the heterotrophic marine microalgae Thraustochytrium pachydermum TSL10 isolated from the sea area of Truong Sa Archipelago, Vietnam - Thom, Le Thi; Ha, Nguyen Cam; Hien, Hoang Thi Minh; Thu, Ngo Thi Hoai; Loan, Vu Thi; Dan, Nguyen Trong; Hai, Truong Ba; Hong, Dang Diem (Vietnam Journal of Biotechnology, 2022)
The sea area of the Truong Sa Archipelago, Vietnam - outpost island region of the country has a special geographical location and plays an important role in economic development as well as security and defense of Vietnam. Here, the first time for isolation of heterotrophic marine microalgae is precious. In this paper, the results on isolation, identification, and selection of suitable culture conditions of the strain Thraustochytrium pachydermum TSL10 isolated from the sea area of Spratly Island, Truong Sa Archipelago, Vietnam in 2021 were presented. The optimal culture conditions for the growth of T. pachydermum  TSL10 in the flask were M1 medium, 3% glucose, 1% yeast extract and 25 - 28 °C temperature. Dry biomass and lipid content reached the highest levels of 12.54 ± 1.23 g/L and 28.65 ± 1.11 % dry cell weight (DCW), respectively. In a 30 L fermentor, T. pachydermum TSL10 grew well in a medium containing 9% glucose and 1% industrial extract yeast. After 120 hours of cultivation, dry biomass, lipid, protein, carbohydrate, carotenoids, and astaxanthin reached the highest levels of 30.76 ± 1.32 g/L; 22.95 ± 0.28% DCW; 6.65 ± 0.19% DCW, 15.96 ± 0.021% DCW, 178.00 ± 2.43 µg/L, and 8.30 ± 0.28 µg/L, respectively. The fatty acid composition contains mainly omega - 6 and omega - 9 fatty acids, accounting for 21.69% of total fatty acids (TFA) and 34.56% of TFA. The fatty acid profile was mainly dominated by linoleic acid and oleic acid, accounting for 21.54% of TFA and 34.23% of TFA, respectively. The results showed that TSL10 biomass was suitable raw material for screening bioactive compounds.